PERALIHAN HARTA ORANG TUA ASUH KEPADA ANAK ASUH PERSPEKTIF HUKUM ISLAM - Azuratunnasuha (PENDALAS: Jurnal Penelitian Tindakan Kelas dan Pengabdian Masyarakat, 2022)
Families who do not have children, not a few who do child care or adoption. Children who are being cared for can be from close family or from other people. Some even take care of children whose origins are unknown. In the case of the transfer of inheritance to foster children, there is also a conflict between biological children and foster children. So this needs to be reviewed as the scope of literacy related to the transfer of the inheritance rights of foster parents to foster children in Islamic law.